2011
DOI: 10.1007/978-3-642-25560-1_10
|View full text |Cite
|
Sign up to set email alerts
|

Finding Non-trivial Malware Naming Inconsistencies

Abstract: Malware analysts, and in particular antivirus vendors, never agreed on a single naming convention for malware specimens. This leads to confusion and difficulty—more for researchers than for practitioners—for example, when comparing coverage of different antivirus engines, when integrating and systematizing known threats, or comparing the classifications given by different detectors. Clearly, solving naming inconsistencies is a very difficult task, as it requires that vendors agree on a unified naming conventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 4 publications
4
24
0
Order By: Relevance
“…Hence, we do not attempt to cover the full range of information that could be quantied from the output of AV scans. In addition, our analysis of antivirus reports has exposed a global lack of consensus that has been previously highlighted by other authors for other computing platforms [2,4,13,33]. Our work cannot be used to solve the challenge of naming inconsistencies directly.…”
Section: Limitations and Future Workmentioning
confidence: 85%
“…Hence, we do not attempt to cover the full range of information that could be quantied from the output of AV scans. In addition, our analysis of antivirus reports has exposed a global lack of consensus that has been previously highlighted by other authors for other computing platforms [2,4,13,33]. Our work cannot be used to solve the challenge of naming inconsistencies directly.…”
Section: Limitations and Future Workmentioning
confidence: 85%
“…The issues of malware naming discrepancies have been debated in security research communities for decades [1,5,12,14,20]. Bailey et al [1] measured such inconsistency in terms of the capability of AV systems to identify similar or identical malware in the same way and found that consistency is never a design goal of most AV systems, e.g., they assign the same name to identically behaved malware only from 31% to 61% of the time.…”
Section: Related Workmentioning
confidence: 98%
“…Bailey et al [1] measured such inconsistency in terms of the capability of AV systems to identify similar or identical malware in the same way and found that consistency is never a design goal of most AV systems, e.g., they assign the same name to identically behaved malware only from 31% to 61% of the time. Recently Maggi et al [20] quantitatively showed that high degrees of inconsistency in terms of naming distance and scatter score exist across different AV systems. Many factors may account for the malware naming discrepancies.…”
Section: Related Workmentioning
confidence: 99%
“…In this Section, we aim to quantify the "inconsistency" typical of multiple AV labels that has been qualitatively discussed in previous work [2,15,18], and analyzed more in details in [1,13]. Our main goal is to suggest that (semi-) manually creating a mapping between malware family labels and correct the inconsistent (or erroneous) labels, which was required in previous work to perform malware cluster validity analysis (e.g., in [2]), is in fact a fairly difficult task.…”
Section: Measuring Inconsistency In Av Labelsmentioning
confidence: 99%